Problematic Internet Use and Its Association with Anxiety, Substance Use, and Academic Performance among Secondary School Students in Nigeria - Oluyemi O Akanni; Ehigiator O Adayonfo (Shiraz University of Medical Sciences, 2020)
Background: Internet addiction is increasingly recognized as a public health concern among children and adolescents. Its psychological and behavioural associates should be closely investigated in Nigeria. The present study aimed to report how prevalent problematic internet use is and examine its associations with psychological problems, such as depression and anxiety, and neuro-behavioural issues like drug use. Methods: Two public and two private schools were selected by convenience. Thereafter, a total of 420 secondary school students were randomly selected to fill a questionnaire. The data collection sheet comprised a socio-demographic section, the WHO Questionnaire for Student Drug Use Survey, Hospital Anxiety and Depression Scale, and the Internet Addiction Test. Frequency was used to determine the prevalence, while a Chi-square and an independent t-test were conducted to examine the relationship between problematic internet use and other variables. Results: A total of 378 questionnaires were analysed. Eighty-eight (23.3%) of the participants had scores indicating problematic internet use. While participants who had cases of anxiety (P<0.001), poor academic performance (P=0.04), used alcohol (P=0.03), and caffeine (P=0.04) over the past 30 days were associated with problematic internet use. Following a logistic regression, only students with cases of anxiety had a significant independent association with problematic internet use (AOR=1.09, 95%CI:1.02-1.16). Conclusions: Problematic internet use is not only common among students, it also has a relationship with commonly occurring worrisome psycho-behavioural variables, requiring further research.